Concretismo brasileiro: a singularidade do movimento construtiro nacional - Cartaxo, Zalinda Elisa Carneiro (1992)
By the end of the forties, it emerges in Brazil a core of reaction against the artistic convenience pattern demonstrated by the remnants of the modernist movement. A group of young artists gets together in the attempt to implement a geometric universal art-compatible with the now industrialized Brazilian society of the fifties. The Swiss Concretism is adopted as a stylistic model and its precepts are adapted to the local circumstances. The different backgrounds of the national and Swiss movements, however, result in different practices. The Brazilian Concretism takes on a singular posture by uniting the principles of the Swiss movement to the ones of the European Constructivism of the beginning of the century, being characterized, in opposition to the Swiss model, as a National Constructivist Project.